Da'wah Through Nasyid to The Millennial Generation (Figure Study of Da’wah of Alfina Nindiyani) - Bobby Rachman Santoso; Mardiyah Habiburrahman (IAIN Tulungagung, 2022)
Da’wah is an effort to invite people to a fitrah. Today da’wah is increasingly diverse in its style. Social media is one of the alternatives for millennial da’wah expansion. Nasyid is one of the media for preaching through poetry. The development of nasyid over time has increasingly changed its style significantly. Currently nasyid, also has relatively large competitiveness in the world of da’wah, especially towards millennials. Alfina Nindiyani ioneon of the murshid who preaches through poetry with its distinctive features and optimization in its presentation so that it can have implications for honey. Researchers in this case use the descriptive qualitative method. This study’s results reveal the role of nasyid in da’wah, the process of the da’wah, and the implication of Alfina Nindiyani’s trough nasyid. It is appropriate that the various kinds of da’wah are presented properly while still looking at the context of their da’wah partners. As a da’i, he must be smart to see and analyze the target of da’wah to achieve success and prosperity.